The study of students' self-assessment using intelligent decision classification (IDC) - Sulaiman, Sarina; Shaari, Nadzari; Salam, Md. Sah; Azwan, Mohamad Nor (Faculty of Computer Science and Information System, 2004)
A Study Of Students Self-Assessment Using Intelligent Decision Classification is to help SPM, STPM or matriculation candidates to choose which courses are suitable for them. This research prototype and knowledge base provides suggestions for the most suitable courses based on the IPT candidates’ interest and their SPM, STPM or matriculations examination result. This research is considered the input factors by users such as interest, and SPM, STPM or matriculation results. This research also help to generate IPT candidates interest by using a technique from Dr Holland, called the SDS (Self Directed Search). Other than that, this research considered other UTM requirements before suggesting suitable courses for the IPT candidates. This is because to ensure that the courses chosen are suitable with their interest and their qualification. The research prototype is developed in Linux Fedora Core 2 operating system using a Hypertext Preprocessor (PHP) programming language, My Structured Query Language (MySQL) and Apache web server to create an expert system by using a knowledge base technique which are rules and backward chaining method as an inference engine. This prototype can be used through Internet so that it can be reached by students from all over Malaysia. In such a way, this will help to attract more IPT candidates joining UTM. Hence, the students will know what courses that are suitable for them based on their interest and qualification.